Management and conservation of Munjal sheep: a threatened sheep population of Northwest India - Yadav, Dinesh Kumar; Arora, Reena; S. Bhatia; Gurmej Singh (Journal of Livestock Biodiversity, 2025)
Despite having better reproductive efficiency, economic importance and distinct identity, Munjal - a mutton-type sheep population of north-western region of India is not recognized as a descript sheep breed. The breeding tract of Munjal sheep was surveyed to study its managemental practices as well as to assess population status. Atotal of 107 random sheep flocks were accessed in their breeding tract and only 32 sheep flocks from three different locations were found to have Munjal sheep. It was observed that farmers were maintaining their flocks under zero-input system. Due to socio-economic and other factors, reduction in breeding tract was observed. The number of animals is continuously dwindling and the current population exhibited its threatened status. Based on field assessment, current population status, inputs provided by the farmers, stakeholders and state animal husbandry and veterinary officers; SWOT analysis on this sheep population was conducted. Accordingly, we suggest improvement and conservation model useful for development of rational breeding and conservation strategies for this important ovine genetic resource of India, which is not an option but an immediate  necessity to check its present scenario of threat to extinction. It is recommended that besides recognizing Munjal sheep as a national sheep breed; the core action of establishing a nucleus flock and implementing it as open nucleus breeding system with exchange of rams between nucleus herd and farmers flocks is warranted immediately